2016
DOI: 10.1002/pat.3971
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cellulose nanofibers and their improvement on ultradrawing properties of ultrahigh molecular weight polyethylene nanocomposite fibers

Abstract: Novel ultrahigh molecular weight polyethylene (UHMWPE)/cellulose nanofiber (CNF) (F100CNFy) and UHMWPE/modified cellulose nanofiber (MCNFx) (F100MCNFxy) as‐prepared nanocomposite fibers were successfully prepared by gel‐spinning F100CNFy and F100MCNFxy gel solutions, respectively. CNF nanofillers with a specific surface area at 120 m2/g and a nanofiber diameter of 20 nm were successfully prepared by proper acid hydrolysis of cotton fibers using sulfuric acid solution. MCNFx nanofillers were prepared by graftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Detailed experimental procedures for preparation of FANC x were reported in our previous investigations [ 29 , 30 , 31 ]. The superscript x denotes the weight ratio of PE-g-MAH to ATANC used in the preparation processes of FANC x particles, and the values of x were 5, 10, 12.5, 15, and 20.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed experimental procedures for preparation of FANC x were reported in our previous investigations [ 29 , 30 , 31 ]. The superscript x denotes the weight ratio of PE-g-MAH to ATANC used in the preparation processes of FANC x particles, and the values of x were 5, 10, 12.5, 15, and 20.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, some investigations found that hydroxyapatite [ 23 , 24 ], graphene [ 15 , 25 ], chitosan [ 26 , 27 ] and bioactive glass [ 28 ] can significantly improve the Young’s modulus, shear modulus, hardness, friction coefficient, or osteogenic properties of the porous UHMWPE. In contrast to hydroxyapatite, graphene, chitosan, or bioactive glass, as a commercial nanoparticle, activated nanocarbons (ANCs) with many hydrophilic active groups on their surface could be commonly used as the reinforcing filler for polymer [ 29 , 30 , 31 ]. However, ANCs are hydrophilic with the water-soluble units, and they are difficult to evenly disperse in hydrophobic UHMWPE during the fabrication process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common purity CO 2 (≥90.0%) was purchased from Wuhan Xiangyun Industry Corporation, Wuhan, China. Detailed experimental procedures for preparation of CNF were described in our previous investigation . The CNF nanofillers have a specific surface area of 120 m 2 /g and a diameter of approximately 20 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] The ultradrawing and ultimate tensile properties of single-stage drawn UHMWPE nanocomposite fibers were favorably influenced by the specific surface areas of the well-dispersed nanofillers. [33] Among these nanofillers, the SA sp of some commercially available activated nanocarbon (ANC) particles are ≥1000 m 2 /g, [33] which are the highest SA sp available in the present market of all nanofillers. The achievable DR and σ t of the most proper single-stage drawn UHMWPE/ functionalized ANC (FANC) fiber reached very high values of 400 and 8.1 GPa.…”
mentioning
confidence: 99%